2011
DOI: 10.1002/jcc.21824
|View full text |Cite
|
Sign up to set email alerts
|

A dissected ring current model for assessing magnetic aromaticity: A general approach for both organic and inorganic rings

Abstract: A model based on classical electrodynamics is used to measure the strength of ring currents of different molecular orbitals, i.e., σ- and π-orbitals, and characteristics of ring current loops, i.e., ring current radii and height of current loops above/below the ring planes, among a number of organic as well as inorganic molecules. For the π-current, the present model represents an improvement of previous approaches to determine ring current intensity. It is proven that the present model is more precise than pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 86 publications
1
59
1
Order By: Relevance
“…Apart from acyclic isomers, the set contains polycyclic structures with rings of different sizes. The sensitivity of NICS values to electron density and ring size excludes NICS‐based indices.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from acyclic isomers, the set contains polycyclic structures with rings of different sizes. The sensitivity of NICS values to electron density and ring size excludes NICS‐based indices.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike with other descriptors, the multicenter index enables one to study almost all types of aromaticity that can be found in the literature, including the all‐metal aromaticity, and it is one of the few descriptors that successfully passed a set of rigorous tests for aromaticity indices, designed by our group . Unfortunately, the calculations of MCI face several challenges such as high computational cost, numerical accuracy problems, ring‐size extensivity issue, and considerable sensitivity to the level of the theory (and even the choice of the exchange‐correlation functional at the DFT level) ,…”
Section: Introductionmentioning
confidence: 99%
“…The large volume of additional information that is required to represent the off‐nucleus magnetic isotropic shielding as a function of position resolves some important criticisms towards single‐point NICS; these include the arbitrariness in the choice of the locations at which such quantities are calculated (NICS can exhibit strong positional dependence, and in certain situations, the standard choices can be inappropriate, see for example, ref. and ref. ) and the fact that a single number might not be sufficient to characterize all aspects of aromatic behaviour, as illustrated by the observation that different ring‐current maps can produce nearly indistinguishable single‐point NICS values …”
Section: Introductionmentioning
confidence: 99%